Proses Produksi dalam Industri Musik Independen di Indonesia - Ningrum Dwi Lestari (Jurnal Komunikasi, 2019)
This research focused on production process in the music recording industry independently by musician, Andien Aisyah. Previously Andien Aisyah worked with Major Label. The concept used in this research is concept of production, and associated with the production process on the recorded music by Andien. The research method used in this research is descriptive qualitative research. The results of the analysis of the production process recording music album by Andien independently has several similar stages to the production process previously with Major Label. In the production process between Major Label and Indie Label there is a difference that is in the pre-production stage, the difference is from the freedom of creativity to create music that will be produced. The freedom is a reason for Andien to move from Major Label to Indie Label. The freedom of creativity on the music recording independently is a form musician resistance against the Major Label which restrict the creativity of their musical works.